Directed infrared emissions of two designed metasurfaces with ceramic arrays - JIANG Wei; WANG Zhihong; HU Yisong; XU Jiansheng; LUO Fa (Xibei Gongye Daxue Xuebao, 2024)
Two metasurfaces of ceramic arrays (A and B) were designed and the 11 μm infrared emission behaviors of them were studied. Both metasurfaces show obvious directed IR emissions. For array A, the radius of inner cylinder R1 and thickness t1 of the ceramics dominate the directional behavior of the IR emissions. The optimized structural parameters are R1=1.0 μm and t1≥1.2 μm with an effective IR emission angle θ in 0°~50 ° and emissivity ε≥0.7 achieved. For array B with Rc=1.05 μm, R1=0.1 μm, t1=0.85 μm, the IR emission is mainly constrained in θ>10°, and an obvious ϕ dependence is observed as θ>40°. The IR emission is higher at ϕ=45° or 135°(±45°) as θ>10° with ε=0.4 at θ=65°. The IR emission is affected by the thickness t1 obviously, with an effective thickness 0.3 μm≤t1≤1.7 μm at Rc=1.0 μm, R1=0.3 μm, and ϕ=0°. For array B with the optimized t1=1.2 μm (ϕ=0°), the IR emission is directed at θ~40° with the emissivity 0.7.